Trends in Qualifying Biomarkers in Drug Safety. Consensus of the 2011 Meeting of the Spanish Society of Clinical Pharmacology - Agúndez, José A.G.; del Barrio, Jaime; Padró, Teresa; Stephens, Camilla; Farré, Magí; Andrade, Raúl J.; Badimon, Lina; García-Martín, Elena; Vilahur, Gemma; Lucena, M Isabel (Frontiers in Pharmacology, 2012)
In this paper we discuss the consensus view on the use of qualifying biomarkers in drug safety, raised within the frame of the XXIV meeting of the Spanish Society of Clinical Pharmacology held in Málaga (Spain) in October, 2011. The widespread use of biomarkers as surrogate endpoints is a goal that scientists have long been pursuing. Thirty years ago, when molecular pharmacogenomics evolved, we anticipated that these genetic biomarkers would soon obviate the routine use of drug therapies in a way that patients should adapt to the therapy rather than the opposite. This expected revolution in routine clinical practice never took place as quickly nor with the intensity as initially expected. The concerted action of operating multicenter networks holds great promise for future studies to identify biomarkers related to drug toxicity and to provide better insight into the underlying pathogenesis. Today some pharmacogenomic advances are already widely accepted, but pharmacogenomics still needs further development to elaborate more precise algorithms and many barriers to implementing individualized medicine exist. We briefly discuss our view about these barriers and we provide suggestions and areas of focus to advance in the field.